Correlation of spectroscopic and structural properties of indocyanine green j-aggregates - D. S. Farrakhova; I. D. Romanishkin; D. V. Yakovlev; Yu. S. Maklygina; V. A. Oleinikov; P. V. Fedotov; M. V. Kravchik; L. Bezdetnaya; V. B. Loschenov (Biomedical Photonics)
Indocyanine green (ICG), when in free form in a liquid, can form stable nanoparticle structures or colloidal solution, while changing its spectroscopic properties. In the work, the aggregation degree and the average size of nanoparticles depending on the concentration of a colloidal solution of indocyanine green (ICG NPs) in the form of J-aggregates were investigated by various methods based on light scattering. The size of nanoparticles is an important parameter from the point of view of clinical application, because the technique of intravenous administration of drugs, in order to avoid microvascular thrombosis and embolism, provides dosage forms with inclusions of individual molecules or their clusters, not exceeding 500 nm diameter. In turn, small nanoparticles less than 30 nm lead to prolonged circulation of the drug in the body with an increased possibility of permeation into cells of healthy tissue. In the course of studies, it was found that an increase in the concentration of ICG NPs in the solution leads to an increase in the average size of spontaneously formed J-aggregates, which, in turn, leads to a decrease in the absorption coefficient in the aggregates. Presumably, this phenomenon, i.e. the established nonlinear dependence of the J-aggregate absorption on its size, can be explained by the formation of absorption centers on the J-aggregate surface in the form of mobile surface molecules. The threshold range of ICG molecule concentration was determined, at which there is a transition from aggregation with an increase in size with a slow addition of ICG J-aggregate molecules in height to a rapid addition in width.